(untitled) (Research, Society and Development, 2022)
Objective: Tracing the profiles of scientific productions prepared by Brazilian nursing professionals or academics during the first year of the COVID-19 pandemic. Methodology: This is an integrative literature review, carried out in August 2020, in the Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS), Google Scholar and Scientific Electronic Library OnLine (SCIELO). Articles written in Portuguese, written by Brazilian nursing professionals or academics, published in the period between January 2020 and August 23, 2020, in national or international journals, were used. Results: A total of 480 articles were found, after methodological rigor through the inclusion and exclusion criteria, 25 articles were selected, being 7 articles in LILACS, 1 in the VHL, 3 in SCIELO and 14 in Google Scholar. The analysis of the articles was performed descriptively and predisposed the data extraction stage: database, authors/month of publication, title/magazine, type of article and topic category. Conclusion: Based on the results found in the literature, it can be observed that nursing is a profession that is directly linked to comprehensive patient care, being one of the categories of health professionals that most stood out within the pandemic scenario, as it is the health workers who were most in contact with patients infected by the coronavirus, and in the midst of this scenario, the challenge of building scientific knowledge about this disease is constituted.